Proposed Performance Management System Design Based on Integrated Performance Management System. Case Study : Pamarican Agro Industry - Zulfikar, Prananda Septian; Wibisono, Dermawan (Journal of Business and Management, 2017)
Abstract-Indonesia is one of the biggest coconut fiber-producer countries in the world beside Philippines, India and Sri Lanka (vdeltafuel, 2016). This condition led to the growth of coconut fiber trader companies and coconut fiber producer companies in Indonesia. Many new companies are emerging to seize this business opportunities. One of these new companies is Pamarican Agro Industry which established in 2016 as a coconut fiber producer company that based in Ciamis, West Java.Ã‚Â Since established in August, 2016 Pamarican Agro Industry does not have any appropriate tools to measure their performance. To become a major player in the market, Pamarican Agro Industry has to increase their competitiveness by evaluating their performance. Therefore, Pamarican Agro Industry owners decide to implement a performance management system for measuring their performance to evaluate the strategy. However, to effectively implement performance management system it is important to understand companyÃ¢â‚¬â„¢s current external and internal conditions and identifies which factors that will affect companyÃ¢â‚¬â„¢s performance. The external conditions consist of factors that are outside the organization and internal conditions consist of factors that are within the organization itself. Moreover, through further companyÃ¢â‚¬â„¢s current conditions analysis researcher is able to select which performance management system frameworks that feasible for the company. The primary data is gathered through discussion, interview and field observation. In this research, the data is gathered by qualitative method through field observation and interview with the owner. Secondary data gathered are vision and mission, organizational structure, production report and financial report. This research used PESTEL Analysis, Resource Based View Analysis, and SWOT Analysis to identify company business condition. After conducting several analyses to determine company condition, researcher found that appropriate performance management system that suitable for Pamarican Agro Industry is Integrated Performance Management System Framework. Therefore, a new performance management framework was developed to be proposed for Pamarican Agro Industry which based on Integrated Performance Management System Framework.Ã‚Â Keyword: Performance Management System, Key Performance Indicators, Integrated Performance Management, Critical Success Factors, Pamarican Agro Industry